Using the Gaia Excess Uncertainty as a Proxy for Stellar Variability and Age - Madyson G. Barber; Andrew W. Mann (The Astrophysical Journal, 2023)
Stars are known to be more active when they are young, resulting in a strong correlation between age and photometric variability. The amplitude variation between stars of a given age is large, but the age–variability relation becomes strong over large groups of stars. We explore this relation using the excess photometric uncertainty in Gaia photometry ( V ar _G , V ar _BP , and V ar _RP ) as a proxy for variability. The metrics follow a Skumanich-like relation, scaling as ≃ t ^−0.4 . By calibrating against a set of associations with known ages, we show how the V ar of population members can predict group ages within 10%–20% for associations younger than ≃2.5 Gyr. In practice, age uncertainties are larger, primarily due to the finite group size. The index is most useful at the youngest ages (<100 Myr), where the uncertainties are comparable to or better than those derived from a color–magnitude diagram (CMD). The index is also widely available, easy to calculate, and can be used at intermediate ages where there are few or no pre- or post-main-sequence stars. We further show how V ar can be used to find new associations and test if a group of comoving stars is a real coeval population. We apply our methods to Theia groups within 350 pc and find ≳90% are inconsistent with drawing stars from the field and ≃80% have variability ages consistent with those derived from the CMD. Our findings suggest the great majority of these groups contain real populations.